As novas tecnologias e o desenho técnico arquitetônico na relação trabalho e educação - (:unkn) unknown (Universidade Federal do Amazonas, 2007)
The present scientific study explains, for grouping systematically, analyzing and understanding the technological innovation knowledge and the technical architectural design in the relationship among work and education, based on Pierre Lévy studies about the future idea in the computation and the knowledge era and Lévy s entirety new view about collective intelligence throughout the anthropology cyberspace. From this logical development on, the study inquires into the several engineer and architectural professional views for retracting together the transformation process of manual design to computer aided design. This study is starting from this dynamic transformation process, for showing the technological innovation action, its tendencies and its givebacks for educational process and the social results in the working world.
Keywords: Tecnologia; Desenho técnico; Trabalho; Educação; Tecnologia; Desenho técnico; Trabalho; Technology; Technical design; Work; Education; CIÊNCIAS HUMANAS: EDUCAÇÃO